MANAJEMEN MUTU TERPADU PADA PROGRAM STUDI MANAJEMEN PENDIDIKAN S2 PASCASARJANA UNIVERSITAS NEGERI JAKARTA - Mukhneri Mukhneri (Jurnal Manajemen Pendidikan, 2010)
At present more directional orientation of the organization to fulfill the needs of customers, both existing customers within and outside the organization. So also with the quality of higher education orientation, which is directed at the needs of the community college (faculty, students, staff) as well as general community needs. The purpose of this study was to describe the implementation process of teaching and learning in higher education, service to students and the system of supervision of learning activities. While the methods used in this research is descriptive method with population research masters student educational management force from 2009 to 2010. The results of the research are as follows : 1) Implementation of the learning process in educational management department have been met, 2) Information on educational management department have also been fulfilled, 3) Service learning resources on educational management department are not entirely satisfied, including the availability of laboratory educational management, 4) Monitoring learning educational management department have been run well.